Library Automation in Indian Central Universities: Issues and Challenges. Issue 4 (19th May 2017) - Ansari, Mehtab Alam; J. N., Gautam; Fatima, Shahwar
ABSTRACT: The purpose of this article is to highlight the status and application of an automated cataloging system in central university libraries in north India. Data has been collected using questionnaires. Interview and observation techniques have also been used to bring objectivity in the present study. Results show that varying levels of progress have been made with respect to implementation of a cataloging system. Results also show that with the help of automation, libraries have satisfied user communities by way of easy retrieval. It has removed discrepancies and set a trend for standardization. Furthermore, staff morale has been boosted up in an automated environment.